2020
DOI: 10.5937/sjm15-19553
|View full text |Cite
|
Sign up to set email alerts
|

The role and importance of large companies in the economy of the Republic of Serbia

Abstract: In contemporary business conditions, advanced market economies are characterized by the increasing contribution of the SMEs sector to the economic development. Having that in mind, a large number of papers have been aimed at analyzing business doing in this sector in the last couple of years. In this way, the focus has been shifted from large business entities and their importance to the economic growth to the SMEs sector. In this regard, the aim of this paper is to examine the financial situation, the place a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 27 publications
(10 reference statements)
1
2
0
Order By: Relevance
“…We found that small FBs with up to 49 employees are less innovative than medium and large FBs with 50 and more employees. This claim is consistent with (Krstić & Fedajev, 2020) assertion that large firms are seen as initiators of innovation activities. Jeng and Pak (2016) also agree with this statement and add that, on the contrary, small firms even lag behind medium-sized firms in a competitive environment.…”
Section: Interpretation Of Results and Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…We found that small FBs with up to 49 employees are less innovative than medium and large FBs with 50 and more employees. This claim is consistent with (Krstić & Fedajev, 2020) assertion that large firms are seen as initiators of innovation activities. Jeng and Pak (2016) also agree with this statement and add that, on the contrary, small firms even lag behind medium-sized firms in a competitive environment.…”
Section: Interpretation Of Results and Discussionsupporting
confidence: 91%
“…According to Krstić and Fedajev (2020), large companies are the driving force of the economy. They often have the financial resources to carry out innovative projects that lead to successful implementation, including legal protection from competition (Vakulenko, 2021).…”
Section: The Size Of Family Businessmentioning
confidence: 99%
“…It enables minimizing the effects of human subjectivity on evaluation outcomes and makes them more realistic (Quan et al, 2021). When using the Entropy method to calculate weights, the following steps are followed (Jin et al, 2020;Krstić & Fedajev, 2020):…”
Section: The Entropy Methodsmentioning
confidence: 99%